High Throughput Screening of Perfumery Raw Materials for Antimicrobial Properties - Rey, Sylvain; Anziani, Pauline; Seyfried, Markus (Combinatorial Chemistry & High Throughput Screening, 2014)
A microdilution protocol was developed and automated using a liquid handling station, allowing the determination of minimum inhibitory concentrations (MIC) of hydrophobic raw materials commonly used in the perfume industry (essential oils and synthetic chemicals). Tests were performed in 96-well microtiter plates against standard bacterial test strains and skin isolates involved in underarm malodor. The comparison with data previously reported in the literature indicated that the protocol was suitable, yielding MIC values that were in general agreement with those derived from manual test methods. For the majority of active test compounds, results showed a pronounced difference in susceptibility pattern between the Gram-positive and Gram-negative test strains used in this study. For a group of acyclic aliphatic aldehydes, a structureactivity relationship depending on the chain length was found.
Keywords: microdilution